Significance of the Practices of the Prophet (Sunna) for Modern People: A Study of the Thought of Bediuzzaman Said Nursi - Zaprulkhan, Zaprulkhan; Kayacik, Ahmet (KALAM, 2018)
This article discusses Nursi’s ideas on significance of the Practices of the Prophet for modern people. In the present day, many modern people deal with some problems such as existential restlessness (existential vacuum), moral degradation, spiritual crisis and so on. On the other hand, according Said Nursi, Practices of the Prophet are all highly beneficial remedies for sicknesses of the spirit, mind, and heart, and particularly for social sicknesses. Accordingly, Practices of the Prophet could give the best solution for modern people problems, both individual sicknesses and social sicknesses.  Before proposing Said Nursi’s perspective about significance of sunna, the paper forwards epistemological questions: How were the meaning and function of sunna according Said Nursi? How are the urgent problems of modern people? What is the significance of Practices of the Prophet for modern people in the view of Said Nursi? The answer of these questions will determine the significance of the Practices of the Prophet in our era and in the future. Accordingly, this paper would be a valuable work for islamic studies since it can make a significanct contribution to Practices of the Prophet as a solution for our problems in the present day and in the future.